Assessment of cigarette butt pollution and its Spatial distribution in Northeastern Iran - Narges Babaei; Fateme Kabirinia; Ali Asghar Nahafpoor; Ziaeddin Bonyadi (Scientific Reports)
Abstract This study investigates the spatial distribution and severity of cigarette butt (CB) pollution in Mashhad, Iran, using the cigarette butt pollution index (CBPI). Sampling was conducted in 25 selected areas, and CB density was calculated for each location. The average CB density across the city was 0.79 CBs/m², with a mean CBPI of 8.89, indicating considerable levels of pollution. The highest recorded CBPI was 28, observed in areas characterized by high population density, commercial land use, and poor ground surface conditions. In contrast, the lowest CBPI was 1.85. Severe pollution (CBPI > 10) was detected in 33.33% of the studied areas. The results revealed that factors such as population density, land use patterns, ground surface quality, annual rainfall, and groundwater proximity significantly influenced CB distribution. A comparison of Mashhad’s CBPI with those of other cities worldwide indicated that while its pollution level is higher than in some Iranian regions, it remains lower than in cities like Santos, Brazil. These findings highlight the urgent need to implement effective management strategies to reduce cigarette butt pollution.